DETECTING trojan virus, PREVENTION STEPS TO YOUR COMPUTER SYSTEM Handling - Yudi Irawan Chandra (JAKSTIK Journal, 2004)
Trojan Horse or better known as the "Trojan" in the computer system is part of a digitalinfection whose presence is not expected by the owner of the computer. Trojan consisting offunctions of unknown purpose, but the outline has destructive properties. Trojans go into acomputer over a network is inserted at the time by surfing with physical media.Trojans do not take effect directly as well as computer viruses, but the potential hazards canbe far greater than computer viruses. Trojans can be activated and controlled by remote orusing the timer. Remote control as well as the Remote Administration Tools, which is theserver version will be controlled by the attacker through his version of the client. Many thingscan be done by an attacker if the victim's computer that has been controlled. Certain unusualports open trojan indicate active eventsHandling Trojan can be done in two ways, namely prevention (preventive) and treatment(recovery). Prevention efforts conducted prior to the occurrence of infection, namely effortsto keep the system has no security holes. Treatment of business conducted after the system isinfected, the effort to close security holes that have been exploited and eliminate the cause ofinfection.Understanding of the nitty gritty of Trojans need to be known by Internet users to avoid orminimize attacks against him and be able to perform the treatment if infected.